Can hypnotherapy entice obese and overweight individuals to improve their dietary intake? - Pei Lin, Lua; Nurul Afiedia, Roslim; Aryati, Ahmad; Mardiana, Mansor; Myat Moe, Thwe Aung; Farrahdilla, Hamzah (2021)
Background: Hypnotherapy has become an increasingly popular alternative option for managing body weight among obese and overweight individuals. However there are still uncertaintes regarding its role in improving dietary intake and weight loss. Objective): To evaluate the effectiveness of hypnotherapy in improving dietary intake and body weight of individuals with excess weight problems in a public university in Terengganu, Malaysia. Materials & Methods: This prospective, pre-and post-intervention randomly assigned participants with body mass index (BMI) ≥ 25.0 kg/m2 to either intervention group (IG=53) or control group (CG=54), for 12 weeks. All participants received health education (diet + exercise + behavioural recommendations) and completed dietary intake (3-day food record), while those in IG undergo additional three hypnotherapy sessions, once a month. Descriptive statistics and repeated measures analysis of covariance (ANCOVA) were utilized (SPSS 23.0). Result: Of the 107 Muslim participants (age = 26.28±8.01; female=82.2%; students=71.0%; BMI=31.39±4.89), 104 of them managed to complete the postintervention phase (drop-out=3). All participants had a significant weight loss (p < 0.001) which did not differ between groups. However, IG participants lost more weight (3.05 kg) than CG (2.11 kg) regardless of time. Findings also revealed that there was significant reduction in total calorie intake among two groups (mean difference = -199.48 kcal, 95% CI: -341.71, -57.27; p < 0.006). Conclusion: Hypnotherapy had positively impact on energy intake, indicating its effectiveness in tackling eating habits. These findings will serve as a basis for future study as one of the alternative approaches in combating weight problems.